MENGGUGAH KREATIFITAS MENGGAMBAR POSTER MELALUI PENUGASAN, PRESENTASI DAN APRESIASI UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SENI BUDAYA SISWA KELAS VIII A SMPN 1 SAWOO PONOROGO - Mohammad Thoyyib (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
One way so that the implementation of Cultural Arts learning can be carried out effectively, namely by assignment, presentation of appreciation as an alternative step in order to streamline and streamline the learning process. The assignment method, appreciation presentation was chosen because in this method students are required to express a lot of ideas freely, of course with the supervision and guidance of the class teacher. The formulation of the problem in this study is: Can learning by exploring ideas / ideas improve students' ability to visualize the form of poster images in the Cultural Arts? This research was conducted at SMP Negeri 1 Sawoo Ponorogo with the object of research being class VIII A students, totaling 40 students. From the results of this study, it can be concluded that learning with the assignment method and presentation of appreciation can improve students' ability to give opinions about the results of creative poster drawings in the subjects of Cultural Arts. This can be seen from the graph calculation. The results of the assessment of the appreciation presentation before and at the end of each class cycle for class VIII A showed a significant increase in learning outcomes in cycle 1 to cycle 2 (71.58-80.0), namely 8.42 points, or 11.76 %. From the data, the percentage increase it can be explained that it turns out that the assignment and presentation methods in this study can improve students' abilities in making creative works and appreciating them